2021
DOI: 10.18632/aging.203569
|View full text |Cite
|
Sign up to set email alerts
|

MSCs enhances the protective effects of valsartan on attenuating the doxorubicin-induced myocardial injury via AngII/NOX/ROS/MAPK signaling pathway

Abstract: Objective: To verify if AngII/NOX/ROS/MAPK signaling pathway is involved in Doxorubicin (DOX)-induced myocardial injury and if mesenchymal stem cells (MSCs) could enhance the protective effects of valsartan (Val) on attenuating DOX-induced injury in vitro . Methods: Reactive oxygen species (ROS) formation and the protein expression of AT1R, NOX2, NOX4, caspase-3, caspase-9 and MAPK signaling were assessed in H9c2 cardiomyocytes exposed to DOX for 24 h in the absence or presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Moreover, AT1R blockade by valsartan downregulated JNK/p38-MAPK through inhibition of AT1R-mediated NADPH oxidase and ROS formation. These findings correspond with previous study demonstrated that valsartan corrected AT1R-induced NOX/ROS/MAPK pathway leading to the prevention of cardiomyocyte hypertrophy ( Cheng et al, 2021 ). To our knowledge, there is no prospective study showed the link between the cardiotoxicity of gefitinib and RAS system.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, AT1R blockade by valsartan downregulated JNK/p38-MAPK through inhibition of AT1R-mediated NADPH oxidase and ROS formation. These findings correspond with previous study demonstrated that valsartan corrected AT1R-induced NOX/ROS/MAPK pathway leading to the prevention of cardiomyocyte hypertrophy ( Cheng et al, 2021 ). To our knowledge, there is no prospective study showed the link between the cardiotoxicity of gefitinib and RAS system.…”
Section: Discussionsupporting
confidence: 93%
“…This finding demonstrates that MAPK signaling pathways is involved in Ang II‐mediated hypertrophic events 59 . The previous studies have also reported that inhibition of NOX activity by an antioxidant led to a significant decrease in the phosphorylation levels of ERK1/2 and p38 in the in vitro study, suggesting that NOX‐mediated ROS production plays a critical role in the activation of MAPK signaling pathways and the development of cardiac injury 11 . In this present study, we found that EA mitigates Ang‐II‐elevated ROS production, thereby inhibiting MAPK activation.…”
Section: Discussionsupporting
confidence: 61%
“…Immoderate production of ROS is believed to be the possible mechanism causing cardiac fibrosis, hypertrophy, apoptosis, and cardiac remodeling in cardiomyocytes induced by Ang-II. 11 Previous studies have shown that activating Ang-II/AT-R1 pathways induces the expression of NOX-derived ROS. Production of ROS stimulates the phosphorylation of p38 and the mitogen-activated protein kinase (MAPK) signaling pathway, leading to myocardial hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Dox activates the motility-related protein 1 (Drp1) by enhancing the expression of NOX1 and NOX4, further inducing mitochondrial division, and causing the NLRP3 inflammasome-mediated pyroptosis in cardiomyocytes [86]. It was found that knockdown of NOX2 and NOX4 can prevent excessive generation of ROS and attenuated DIC [87,88].…”
Section: Nox Singnalingmentioning
confidence: 99%